Santo Estêvão de Chaves : uma nova inscrição do Bispo D. Pedro - Barroca, Mário Jorge (2014)
Study of two medieval inscriptions of Santo Estêvão de Chaves, a church in the North of Portugal: one of 1089 (AD), celebrating the Dedication of the temple; the other one, of 1294 (AD), celebrating the rebuilding of the church. The oldest inscription, which corresponds to the dedication officiated by the Bishop D. Pedro (1071-1091), is contextualized in the earliest medieval documentation of Santo Estêvão de Chaves and in the other dedication ceremonies known to the Bishop of Braga